Bimetallic Ag–Cu-trimesate metal–organic framework for hydrogen sulfide removal. (23rd November 2021) - Gupta, Nishesh Kumar; Bae, Jiyeol; Kim, Kwang Soo
Abstract : Bimetallic Ag-Cu-trimesate metal-organic framework was fabricated for H2 S mineralization. The MOF was partially regenerated using H2 O2  solution for five cycles. Abstract : Here, we have fabricated a bimetallic Ag–Cu-trimesate metal–organic framework at room temperature. The MOF showed rod-like morphology with a uniform distribution of Ag and Cu-sites in the MOF. The MOF has a surface area of 27.2 m 2 g −1 with a mean pore diameter of 3.8 nm. The X-ray photoelectron (XPS) analysis confirmed the presence of Ag(i ), Cu(i ), and Cu(ii ) sites in the MOF. Moreover, a minor fraction of Ag as Ag 0 (27.2%) was confirmed due to the reductive effect of DMF solvent. The synthesized MOF was tested for H2 S removal under ambient conditions, where a maximum adsorption capacity of 69.7 mg g −1 was achieved. A novel regeneration method based on H2 O2 solution partially regenerated the MOF. The diffraction pattern predicted the exceptional stability of the MOF after the adsorption–regeneration process. The XPS analysis confirmed sulfate/bisulfate (82.6%) and sulfide (17.4%) as the H2 S adsorption/oxidation species. The regeneration process involved the oxidation of Ag 0 and Cu(i ), which resulted in appreciable adsorption capacity in the subsequent cycles. Thus, we have reported a new and economical synthesis of bimetallic MOFs and a method for the partial regeneration of the spent MOF.